Mystical Symbolism of Allama Iqbal Lahori and Shaikh Mahmoud Shabistari - Nabiollah Masoumi; Moch. Nur Ichwan; Dicky Sofjan (UNHI PRESS, 2023)
One of the most important sources for the mystical philosophy of the Sufis is “Gulshan-i Raz” (The Rose Garden of Mystery) of Shaikh Mahmoud Shabistari, written in the 14th century. Shabistari not only explained the doctrines of the Persian Sufis in these famous treaties, but also explained some of the main symbols of Sufi literature. Six hundred years after Shabistari, Allamah Iqbal Lahori (1877 - 1938), wrote a new book with the same name “Gulshan-i Raz-i Jadid” (The New Rose Garden of Mystery), revising the Sufi doctrine of Shabistari and traditional Persian Sufis. The three chapters of Shabistari’s Gulshan-i Raz, dedicated to Sufi symbology, are removed from the book of Allama Iqbal. Therefore, this paper aims to compare the poetic symbolism of Iqbal with the symbols used by Shabistari. The comparison would examine whether Iqbal agreed with the last three chapters of Shabistari’s book on Sufi symbolism or if he did not find the symbols relevant to his new mystical doctrine.